Seasonality and nutrition-sensitive farming in rural Northern Ghana - de Jager, Ilse; van de Ven, Gerrie W. J.; Giller, Kenneth E.; Brouwer, Inge D. (Springer, 2023)
In rural sub-Saharan Africa, where malnutrition in all its forms is rife, the greatest gap between the availability of foods and the foods needed for a nutritious diet are faced during the ‘hunger season’. We investigated what rural households in Northern Ghana would need to grow to ensure year-round availability of a nutrient adequate diet or the income required to fulfil their dietary needs. We applied linear programming to model different scenarios and interventions. Our results provide three major insights. First, considering seasonality is crucial in nutrition-sensitive farming. Ensuring a nutritious diet year-round requires enhanced availability of vegetables and fruits throughout the year. Second, although staple crops do not provide the full range of essential nutrients, increasing their yields allows for a reduction of field size, freeing up space for the production of other foods belonging to a nutritious diet, such as vegetables. Third, small farms are unable to produce sufficient food to cover their needs. They depend on income both from agriculture and other sources, and the availability of types of foods on markets to meet their dietary needs. Our study shows the value of modelling the range of dietary effects from agricultural interventions in a specific context, using a local feasible nutritious diet as a starting point and taking seasonality into account.